Health risk assessment of heavy metals exposure in household dust: relationships between heavy metals concentrations, household characteristics and daily living activities among residents in Kampar, Malaysia - Low, Yi Chen; Guo, Xinxin; How, Vivien; Wai, Soon Han; Norbäck, Dan; Lim, Fang Lee (Springer International Publishing, 2025)
Heavy metals (HM) emitted from anthropogenic activities pose serious environmental and health risks. However, limited research has been conducted on their health risks in former tin mining towns in Malaysia, such as Kampar. Therefore, this study aims to assess the health risk of HM exposure in household settled dust and to investigate the relationships between residents’ daily activities and the concentration of HM in household dust in Kampar town, Malaysia. Survey questionnaires were distributed to the respondents (n = 200) from 51 households to collect their demographic data, household characteristics, and daily living activities. Household settle dust was collected from respective households using handheld vacuum cleaner, and concentrations of 10 HM (As, Zn, Fe, Ni, Pb, Al, Cd, Cu, Cr, Mn) in dust samples were measured using inductively coupled plasma optical emission spectrometry (ICP-OES). Non-carcinogenic risk and carcinogenic risk for HM exposure were estimated using Hazard Index (HI) and Total Lifetime Cancer Risk (TLCR), respectively. Associations of daily activities and concentrations of HM were analyzed using multi-level linear mixed model. The findings showed HI of arsenic exposure in children exceeded the acceptable threshold level (HI: 1.20). The carcinogenic risks of assessed HM were within the tolerable threshold of 1 × 10−4 to 1 × 10−6. The presence of houseflies and mosquitoes was positively associated (p < 0.05) with concentrations of Cd (OR: 1.182) and Zn (OR: 1.757) in household dust. Frequent smoking (OR: 1.173), burning incense/mosquito coil/candle (OR: 1.202), and pan-frying practices (OR: 1.100) were positively related (p < 0.05) with higher concentrations of HM. However, the mitigation approaches like the use of air purifier (ORs: 0.698–0.763) and frequently vacuuming floor (OR: 0.899) significantly (p < 0.05) reduced the HM concentration. The daily practices and cleaning activities of building occupants were significantly related with their HM exposure in household settled dust.